Comparison and evaluation of South African poletop designs for 11kV and 22kV rural distribution lines - Scott, R A (University of Cape Town, 2014)
Bibliography: leaves 155-160. === The ultimate purpose of this thesis is to compare and evaluate. South African poletop designs for 11kV and 22kV rural distribution lines. However, a frame of reference is first established from the literature and from construction practice before the analytical stage is tackled. In 1989, when the work for this thesis was started, it was quite apparent that there existed a proliferation of configuration designs for rural overhead lines at 11 kV and 22kV in South Africa. The electricity supply industry did not use a universal configuration. Eskom supplied over 97 of South Africa's electricity in 1990 (Eskom, 1990). It was also operating 160 280km of lines at 22kV and below in that year and was largely responsible for this situation. Local supply authorities or distributors S!JCh as municipalities either bought components from Eskom or used an Eskom design, or developed their own designs internally or via consultants. In any event, the designs they used are not considered to be a significant portion of the total. Historically, Eskom developed on a strongly regionalised basis, the separate Undertakings joining up (electrically) to form the national grid in 1973. Prior to 1985 there were six Regions distributing the electricity generated by the power stations. Each Region developed its own designs, independently or based on designs imported from Britain.